2019
DOI: 10.1108/ijif-10-2018-0114
|View full text |Cite
|
Sign up to set email alerts
|

Interest-free microfinance in India: a case study of Bait-un-Nasr Urban Cooperative Credit Society

Abstract: Purpose The purpose of this paper is to understand interest-free microfinance practices in India, identify issues and recommend possible solutions. Design/methodology/approach To achieve the proposed objectives, Bait-un-Nasr (BuN) Urban Cooperative Credit Society, located in Mumbai, India, is considered for the case study. The study is based on both primary and secondary data. The primary data are collected through questionnaires and secondary data from various sources. Performance of the institution is asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…In addition, this study reveals that dependence on one funding source, namely membership fees, has a significant effect on the unsustainability of IMFI. Shaik Mohammed and Waheed, 2019a , Shaik Mohammed and Waheed, 2019b examined some of the problems faced by IMFI's in India, namely the potential liquidity risk, the lack of service coverage and not being able to reach the inferior, issues of Shariah compliance, as well as problems in the structure of group savings schemes and financing contracts on Profit-sharing. In addition, in another study, Shaik Mohammed and Waheed, 2019a , Shaik Mohammed and Waheed, 2019b found that the performance of IMFI's in India, in this case, the Bait-un-Nasr (BuN) Urban Cooperative Credit Society located in Mumbai, is still below the performance standards of conventional MFI's.…”
Section: Existing Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this study reveals that dependence on one funding source, namely membership fees, has a significant effect on the unsustainability of IMFI. Shaik Mohammed and Waheed, 2019a , Shaik Mohammed and Waheed, 2019b examined some of the problems faced by IMFI's in India, namely the potential liquidity risk, the lack of service coverage and not being able to reach the inferior, issues of Shariah compliance, as well as problems in the structure of group savings schemes and financing contracts on Profit-sharing. In addition, in another study, Shaik Mohammed and Waheed, 2019a , Shaik Mohammed and Waheed, 2019b found that the performance of IMFI's in India, in this case, the Bait-un-Nasr (BuN) Urban Cooperative Credit Society located in Mumbai, is still below the performance standards of conventional MFI's.…”
Section: Existing Researchmentioning
confidence: 99%
“…In addition, this study reveals that depending on one source of funding, namely member fees contribute significantly to the unsustainability of IMFI. Shaik Mohammed and Waheed, 2019a , Shaik Mohammed and Waheed, 2019b The problems faced by IMFI in India, namely the potential liquidity risk, the lack of coverage among the poorest of the poor, the problem of Shariah in the method of determining service fees, and problems in the structure of group savings schemes and financing contracts for the result. Shaik Mohammed and Waheed, 2019a , Shaik Mohammed and Waheed, 2019b IMFI's performance in India is still below the performance standards of conventional MFIs.…”
Section: Poverty Alleviationmentioning
confidence: 99%
“…In providing interest-free banking funds to its customers, Bait-un-Nas'r is evaluated on the basis of economic and sustainability aspects. This study also aims to raise society's awareness of interest-free banking (Shaik & Waheed, 2019).…”
Section: Evidence Based Case Study On Bait-un-nas'r Mumbai Indiamentioning
confidence: 99%
“…MicroFinance Institutions (MFIs) are institutions that provide financial services for microentrepreneurs and low-income communities that relatively have complete products following the needs of low-income people (Dewi, 2017;Mohammed and Waheed, 2019). Many types of MFIs in Indonesia are overgrowing and essential in improving the community's economy.…”
Section: Introductionmentioning
confidence: 99%